2022
DOI: 10.1177/00139165221131002
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Environmental Attitudes, Environmental Efficacy, and Pro-Environmental Behaviors Across and Within 11 Countries

Abstract: Pro-environmental behaviors (PEBs) are crucial to reducing environmental degradations, and much research has focused on two key psychological antecedents: pro-environmental attitudes and efficacy beliefs. Yet, the evidence of their direct and interactive relationships are mixed. Further, few studies investigate how these key relationships vary across different countries and contexts. Using data from a large international survey ( N = 11,000) in 11 countries, we examine relationships among environmental attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 95 publications
1
2
0
1
Order By: Relevance
“…In this study, the respondents showed a positive attitude toward the intention to implement pro-environmental policies (mean on a scale of 1-5, with high numbers representing a positive attitude, 4.182). Moreover, the results of this study are also in line with other studies involving assessments of factors affecting the intention to implement pro-environmental behaviors (see Janmaimool and Khajohnmanee, 2019;Miller et al, 2022).…”
Section: Utilization Of Cotabato City Riverssupporting
confidence: 90%
“…In this study, the respondents showed a positive attitude toward the intention to implement pro-environmental policies (mean on a scale of 1-5, with high numbers representing a positive attitude, 4.182). Moreover, the results of this study are also in line with other studies involving assessments of factors affecting the intention to implement pro-environmental behaviors (see Janmaimool and Khajohnmanee, 2019;Miller et al, 2022).…”
Section: Utilization Of Cotabato City Riverssupporting
confidence: 90%
“…Ob sich umweltrelevante Haltungen und Überzeugungen in tatsächliches Handeln umsetzen, ist von verschiedenen Einflussfaktoren abhängig (Miller et al, 2022). Nachhaltigkeitsorientiertes und ethisches Kaufverhalten Jugendlicher kann als ein Teilelement des allgemeinen nachhaltigkeitsorientierten Verhaltens betrachtet werden.…”
Section: Selbstberichtetes Umweltverhalten Jugendlicherunclassified
“…In brief, females tend to be aware and caring regarding the needs of others and then carry out an ethic of care that values accountability and relationships. Those prosocial or pro-environmental attitudes are crucial antecedent to relevant intentions and behaviors (Miller et al, 2022).…”
Section: Related Literaturementioning
confidence: 99%